Influence of ABS print parameters on a 3D open-source, self-replicable printer - Alves Guimarães, André Luiz [UNESP]; Gerlin Neto, Vicente [UNESP]; Foschini, Cesar Renato [UNESP]; dos Anjos Azambuja, Maximiliano [UNESP]; Hellmeister, Luiz Antonio Vasques [UNESP] (Emerald, 2020)
Purpose: The purpose of this paper is to investigate and discuss the influence of printing parameters on the mechanical properties of acrylonitrile butadiene styrene (ABS) print by fused deposition modelling (FDM). The mechanical properties of ABS are highly influenced by printing parameters, and they determine the final product quality of printed pieces. Design/methodology/approach: For the paper’s purpose, five main parameters (extrusion temperature, infill pattern, air gap, printing speed and layer thickness) were selected and varied during ABS printing on an open-source and self-replicable FDM printer. Three different colors of commercially available ABS were also used to investigate color and printing parameter’s influence on the tensile strength. Findings: The research results suggest that two parameters (infill pattern and layer thickness) were most influential on the mechanical properties of print ABS, being able to enhance its tensile strength. Another key influential factor was material color selected prior to printing, which influenced the tensile strength of the print specimen. Originality/value: This study provides information on print parameters’ influence on the tensile strength of ABS print on replicable open-source three-dimensional (3D) printers. It also suggests the influence of materials’ color on print pieces’ tensile strength, indicating a new parameter for materials selection for 3D printing.
Keywords: ABS; FDM; Filament color; Mechanical properties; Open source; Print parameters